The Paradox of Native Americans in Black Elk Speaks - Arido Laksono (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Black Elk Speaks is a book describing the spirituality and social life of Native Americans. It contains values of living in balance with nature and the respect towards the Great Spirit. Black Elk himself is a prominent figure believed by Native Americans or the Indian as having vision of the future. The book is the words of Black Elk as told through John G. Neihardt (Flamming Rainbow). By reading the book, we learn how Native Americans survive in the land that does not belong to their tribes. The pain and sorrow of watching relatives and family vanished in the war. Yet, the identity of Native Americans remains among the uproar of social changes in the history of America. The purification of mind and soul in viewing modern life is in line with the American individualism. Furthermore, the study of Native American literature will enrich the spiritual journey of individuals in interpreting life in a multicultural society. Here, I would like to explore the paradox of living in the Indian reservation and the facts faced by Native Americans as told in Black Elk Speaks. Keywords: Black Elk, vision, spirituality, paradox, Native Americans